Actividades lúdicas y motricidad gruesa en niños de 4 a 5 años de la Escuela de Educación Básica Fiscal Filomena Mora de Carrión de la ciudad de Loja en el periodo 2023 – 2024. - Gonzalez Vega, Yuri Michaela (2024)
Gross motor skills refer to the ability to perform movements associated with the larger muscles of the human body. These are physical skills and abilities that develop from childhood, enabling individuals to engage in activities without difficulty. Therefore, this study aimed to determine the impact of recreational activities on the development of gross motor skills in children aged 4 to 5 years at Filomena Mora de Carrión Elementary School. To achieve this, a quasi-experimental research design was used with a mixed approach and descriptive scope. Additionally, the inductive-deductive method was employed for drawing conclusions, and the analytical-synthetic method was used for drafting the theoretical framework. To assess gross motor skills, the Preschool Psychomotor Assessment Scale (EPP) was administered to a sample of twenty-two children. The results showed that 85.80% of the sample fell into the low-level category, while 14.20% were at a normal level, with difficulties in areas such as locomotion, positioning, balance, and coordination of hands, upper and lower limbs. Therefore, strategies are needed to address the identified weaknesses in the studied population. Furthermore, an alternative proposal consisting of 25 recreational activities is suggested, which can be implemented in the classroom and on the school playground. These recreational activities significantly impact the development of gross motor skills in children, contributing to maintaining good physical and mental health. Keywords: Psychomotricity, play, balance, movement, coordination.